Decreased Resting-State Functional Connectivity of Periaqueductal Gray in Temporal Lobe Epilepsy Comorbid With Migraine - Wang, Long; Cai, Xin-Ting; Zu, Mei-Dan; Zhang, Juan; Deng, Zi-Ru; Wang, Yu (Frontiers in Neurology, 2021)
Objective: Patients with temporal lobe epilepsy (TLE) are at high risk for having comorbid condition of migraine, and these two common diseases are proposed to have some shared pathophysiological mechanisms. Our recent study indicated the dysfunction of periaqueductal gray (PAG), a key pain-modulating structure, contributes to the development of pain hypersensitivity and epileptogenesis in epilepsy. This study is to investigate the functional connectivity of PAG network in epilepsy comorbid with migraine. Methods: 32 TLE patients, including 16 epilepsy patients without migraine (EwoM) and 16 epilepsy patients with comorbid migraine (EwM), and 14 matched healthy controls (HCs) were recruited and underwent resting functional magnetic resonance imaging (fMRI) scans to measure the resting-state functional connectivity (RsFC) of PAG network. The frequency and severity of migraine attacks were assessed using the Migraine Disability Assessment Questionnaire (MIDAS) and Visual Analogue Scale/Score (VAS). In animal experiments, FluoroGold (FG), a retrograde tracing agent, was injected into PPN and its fluorescence detected in vlPAG to trace the neuronal projection from vlPAG to PPN. FG traced neuron number was used to evaluate the neural transmission activity of vlPAG-PPN pathway. The data were processed and analyzed using DPARSF and SPSS17.0 software. Based on the RsFC finding, the excitatory transmission of PAG and the associated brain structure was studied via retrograde tracing in combination with immunohistochemical labeling of excitatory neurons. Results: Compared to HCs group, the RsFC between PAG and the left pedunculopontine nucleus (PPN), between PAG and the corpus callosum (CC) was decreased both in EwoM and EwM group, while the RsFC between PAG and the right PPN was increased only in EwoM group but not in EwM group. Compared to EwoM group, the RsFC between PAG and the right PPN was decreased in EwM group. Furthermore, the RsFC between PAG and PPN was negatively correlated with the frequency and severity of migraine attacks. In animal study, a seizure stimulation induced excitatory transmission from PAG to PPN was decreased in rats with chronic epilepsy as compared to that in normal control rats. Conclusion: The comorbidity of epilepsy and migraine is associated with the decreased RsFC between PAG and PPN.